PENGENDALIAN TERPADU PENYAKIT KARAT TUMOR PADA TANAMAN SENGON (PARASER/ANTHESFALCATAR/A)DI HUTAN RAKYAT, KECAMATAN PRINGSURAT,TEMANGGUNG, JAWA TENGAH - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Gall rust disease caused by gall rust fungus (Uromycladium tepperianum), is one of the most devastate disease of sengon (Falcataria moluccana (Miq.) Barneby & J.W. Grimes) both in plantation and community forest in Indonesia. Status of the disease,particularly in Java island have been at epidemic level. Integrated gall rust disease management control using some appropriate techniques regarding pruning practice, applying fertilizer, applying fungicide before and during new planting, also application fungicide of gall at the coppice stem have been conducted. Applying 200 g/trees of NPK fertilizer on 2 years age of sengon trees combine with cassava,coffee and papaya at the community forest able to significantly reduce the incidence of gall rust disease at the stem. Pruning practice is able to reduce about 30%- 40%of gall rust disease incidence after four month application. Aplication using systemic fungicide before and during planting were able to reduce 33%to 45%gall rust disease in the new planting of sengon in the field. However, application of fungicide every one week on the coppice stem, were not successful to reduce gall development after two times application.